Further considerations concerning CAVAT. Issue 4 (2nd August 2021) - Price, Colin
ABSTRACT: The amenity tree valuation method CAVAT apparently gives reduced weight to future benefits, similarly to discounting. Discounting future conditions allows calculation of a value per year per square centimetre of tree basal area, on the premise that tree planting was rationally done. The resulting value ascribed to a target tree is much lower than that calculated by CAVAT. CAVAT's value is the same as given by the "rational" procedure if trees were predicted not to grow. The "rational" perspective provides a reasoned estimate of CAVAT's avowed objective of calculating a compensation replacement value for lost trees. CAVAT itself seemingly calculates over-generous compensation. The "rational" protocol's apparently low value may be adjusted upwards to recognise incomplete planting survival, conditions of high cost, overheads and, sometimes, defective discounting. These, and any neglect of the value of subsequent replanting and of people's particular associations with trees, may undervalue fair financial recompense, especially when no compensation planting is made. However, some of these factors would revise CAVAT values upwards too, so the gap between outcomes might remain. Neither protocol translates from a cost basis to a full amenity benefit of trees.